(untitled) (Prithvi Journal of Research and Innovation, 2023)
This paper analyzes the recent trend of branding the hotels and restaurants with local names in Lakeside of Pokhara, Nepal. The place is a major tourist hub that targets both domestic and foreign tourists, using buildings, hoarding boards, language and ambience of restaurants and hotels that have set up their business with western cultures. The unique standpoint of local branding has ignited this study with thirst to know the answers of the questions such as what has tempted the entrepreneurs to local branding, if such branding resists the global cultures and creates unique business space. Using purposive and convenient sampling method, the participants have been selected. Following ethnographic research design, the field was observed and the participants were interviewed along with the library study for the theoretical concept of branding, globalization, localization, and glocalization. Analysis of data is thematic. This paper argues that there are multiple reasons behind branding the tourism businesses with local names but they ultimately create a local cultural space for business. Such cultural space resists global cultures and maintains local cultural identity. Yet the created local space is not purely local.